Mutual Fund Trading, Fund Flows, and ESG Portfolios - Albuquerque, Rui; Koskinen, Yrjö; Santioni, Raffaele (Journal of Financial and Quantitative Analysis, 2026)
This article studies how ESG and conventional mutual funds trade stocks during the COVID-19 crash. Both fund types trade individual stocks similarly: Net purchases of ESG stocks are less sensitive than other stocks to fund flows pre-crash, but sensitivities increase for all stocks during the crash. In contrast, ESG funds’ aggregate net purchases are less sensitive than those of conventional funds during the crash. This difference is due to ESG funds’ portfolio tilt toward the less flow-sensitive ESG stocks. There is no evidence of an ESG clientele effect in trading decisions, as both fund types trade individual stocks similarly.